ETIKA MEDIA DALAM PILKADA : SIARAN â€œKAMPANYEâ€ DI TELEVISI LOKAL - Lukmantoro, Triyono; Rakhmad, Wiwied Noor; Ibrahim, Evie S. (JURNAL ILMU SOSIAL, 2013)
The aim of this research was to describe the understanding and ethical considerations of media professionals in the coverage of Central Java governor election. This research showed that Code of Journalism Ethics (Kode Etik Jurnalistik) can be used by journalists as moral guidance. The journalists prefered to consider news values and society interests in presenting the news. beside that, the journalists choose the flexible action in order to accomodate the interests of extra-media environment and media owner.